Mapping The Implementation of The Ethnoscience Approach In Early Childhood Education To Improve Children's Science Skills In Mataram City - Filsa Sativa; Baik Nilawati Astini; Ika Rachmayani; Aulia Dwi Amalina Wahab; Baiq Nada Buahana (BIOCHEPHY: Journal of Science Education, 2026)
This study aimed to describe the implementation of the ethnoscience approach in early childhood education and to identify teachers' competence in applying it. A descriptive quantitative method was employed, complemented by Focus Group Discussions (FGDs) to validate the data and research findings. A total of 161 early childhood education teachers in Mataram City were selected through purposive sampling. Data were collected using observations, questionnaires, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of ethnoscience varied across districts. Ampenan and Mataram achieved a good category (72%) by integrating local culture through project-based and experimental learning activities. Meanwhile, Selaparang (70%), Cakranegara (70%), Sekarbela (69%), and Sandubaya (68%) were classified as fairly good due to teachers' limited understanding, insufficient training, and the continued use of conventional teaching methods with minimal integration of local culture. Overall, the implementation of ethnoscience was reasonably effective; however, further professional development, mentoring, and the development of instructional media and learning models are needed to ensure more equitable and effective implementation.